Pediatric isoniazid-resistant tuberculosis of the bone marrow manifesting as hemophagocytic syndrome: A case report - Zheng, Junfeng; Xu, Yongbin; Yang, Jun; Cao, Ke; Deng, Guofang; Zhang, Peize (Frontiers in Pediatrics, 2022)
Hemophagocytic syndrome (HPS) is a critical syndrome of ineffective hyperinflammatory immune response resulting in infiltration of lymphocytes and histiocytes in various organs. Causes can be hereditary or due to malignancy, autoimmune disease or infection. HPS due to mycobacterium tuberculosis is rare. Only a handful of cases are reported, and they are mostly associated with severe disseminated TB. We reported a 9-year-old boy with tuberculosis of the bone marrow accompanied with hemophagocytic syndrome. The patient presented with manifestation of HPS, no respiratory symptoms or risk factors for TB but was later diagnosed of isoniazid-resistant TB in the bone marrow. He had a good outcome after receiving anti-TB drugs and corticosteroids in time. This case highlights that bone marrow might be a shelter for Mycobacterium tuberculosis. Concurrent testing for drug susceptibility in TB cases with an uncommon manifestation is recommended even for first episodes. Early diagnosis and etiological confirmation of the infection origin and appropriate treatment are essential to improve survival in this otherwise life-threatening condition.